Use and abuse of the monopoly press in Singapore : a view of SPH. - Koh, Anna Suan Gek. (2009)
This research has shown that although the monopoly press in Singapore exhibits certain uses, it also habours many abuses that must be arrested. The researcher recommends that elimination of the monopoly will do much good for readers and advertisers. This paper first shows that the local newspaper industry demonstrates significant qharacteristics of a monopoly, and that the monopolistic situation arises out of the presence of barriers to entering the newspaper market. As a monopoly, the press is able to be economically independent, resisting pressures from advertisers. As a huge conglomerate, the press enjoys many benefits of a big business; for example, offering training and career opportunities to attract high calibre staff and economies of scale. It also has a greater bargaining power when negotiating costs of wire services and the purchase of newsprint and equipment. The press monopoly status allows advertisers to reach a wide segment of potential consumers, thereby lowering the cost to reach every 1,000 readers (CPM). However, the monopoly power can also be abused; some of the consequences are unintentional effects, others are misuse of power. One of the most prominent abuse of the monopoly press is the increment of advertising content, and thereby reduction of news. Research has revealed that competition spurred the press to generate more local news and not merely to lift off news articles from the wire services. As the newspaper industry has only one player, news content suffers from a lack of diversity; the problem is compounded by the close relationship between the government and the press. As a monopolistic high- investment business, the newspaper firm experiences many conflict of interests that resulted in advertisers being treated unfairly. The huge profits and competition-free environment has resulted in the press bordering on complacency. The presence of certain uses of the monopoly press does not erase the dire consequences that have been inflicted on readers and advertisers. This paper recommends that a competitive press can serve readers and advertisers better as a newspaper in competition can still enjoy the uses of a monopoly.